Densification of PZN-10PT ceramics from powders obtained by the combustion reaction synthesis (2014)
((1-x)Pb(Zn1=3Nb2=3)O3-xPbTiO3-PZN-xPT) single crystals with perovskite structure near to the morphotropic phase boundary (MPB), x_0; 09, exhibit unusual large dielectric and piezoelectric constants. Preparation of PZN-PT ceramics with composition near to